SYSTEM OF VOCATIONAL AND HIGHER EDUCATION IN GERMANY (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article discusses specific aspects of the secondary higher education system in Germany. Types of schools in primary and secondary education are covered.